2018
DOI: 10.3390/ijerph15050989
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and Temporal Trends of Perfluoroalkyl Substances in Pregnant Women: The Hokkaido Study on Environment and Children’s Health

Abstract: Perfluoroalkyl substances (PFAS) are persistent bio-accumulative chemicals that impact the health of pregnant women and their children. PFAS derive from environmental and consumer products, which depend on human lifestyle, socioeconomic characteristics, and time variation. Here, we aimed to explore the temporal trends of PFAS in pregnant women and the characteristics related to maternal PFAS concentration. Our study is part of the Hokkaido Study on Environment and Children’s Health, the Hokkaido large-scale co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 47 publications
4
30
2
Order By: Relevance
“…We also observed an inverse association between maternal levels of specific PFAS and the number of previous deliveries, due to transfer of PFAS to the fetus, and excretion via breast milk (i.e., breast feeding) which is in line with earlier reports 37,38 . Interestingly, pooled analysis across multiple studies suggests that increasing birth order is associated with lower risk of T1D 52 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We also observed an inverse association between maternal levels of specific PFAS and the number of previous deliveries, due to transfer of PFAS to the fetus, and excretion via breast milk (i.e., breast feeding) which is in line with earlier reports 37,38 . Interestingly, pooled analysis across multiple studies suggests that increasing birth order is associated with lower risk of T1D 52 .…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with previous studies 37,38 , we observed inverse correlations between the number of previous deliveries and levels of specific PFAS: PFOA (r = -0.44, FDR q < 0.01), PFHpS (r = -0.39, q < 0.01), PFOS (r = -0.31, q = 0.07), total PFAS (r = -0.26, q = 0.23, nominal p = 0.006).…”
Section: Metabolic Profiles In Mothers Associate With Pfas Exposuresupporting
confidence: 94%
“…PFAS levels varied between different maternal characteristics including maternal delivery age, pre-pregnant BMI, parity, maternal education level, smoking status, alcohol consumption history, and annual household income. Numerous epidemiological studies have reported associations between prenatal PFAS exposure and adverse health outcomes [259].…”
Section: Pregnant Women and Developmental Consequencesmentioning
confidence: 99%
“…PFAS levels varied between different maternal characteristics including maternal delivery age, pre-pregnant BMI, parity, maternal education level, smoking status, alcohol consumption history, and annual household income. Numerous epidemiological studies have reported associations between prenatal PFAS exposure and adverse health outcomes [256].…”
Section: Pregnant Women and Developmental Consequencesmentioning
confidence: 99%